A Y374X TDP43 truncation leads to an altered metabolic profile in amyotrophic lateral sclerosis fibroblasts driven by pyruvate and TCA cycle intermediate alterations - Allen, Scott P.; Al Sultan, Afnan; Kabucho Kibirige, Elaine; Tonkiss, Erin; Hamer, Keaton J.; Castelli, Lydia M.; Lin, Ya-Hui; Roscoe, Sarah; Stefanidis, Nikolaos; Mead, Richard J.; Highley, J. Robin; Cooper-Knock, Johnathan; et al. (Frontiers in Aging Neuroscience, 2023)
A p.Y374X truncation in TARDBP was recently shown to reduce expression of TDP43 in fibroblasts isolated from ALS cases. In this follow up study focused on assessing the downstream phenotypic consequences of loss of TDP43 in the context of the truncation, we have shown a striking effect on the fibroblast metabolic profile. Phenotypic metabolic screening uncovered a distinct metabolic profile in TDP43-Y374X fibroblasts compared to controls, which was driven by alterations in key metabolic checkpoint intermediates including pyruvate, alpha-ketoglutarate and succinate. These metabolic alterations were confirmed using transcriptomics and bioenergetic flux analysis. These data suggest that TDP43 truncation directly compromises glycolytic and mitochondrial function, identifying potential therapeutic targets for mitigating the effects of TDP43-Y374X truncation.